Measurement of gallbladder volume by ultrasomography in pregnant women - Sait KAPICIOĞLU; Sevgi GÜRBÜZ; Ahmet DANALIOĞLU; Ömer ŞENTÜRK; Ercüment OVALI; Mehmet USLU (Turkish Journal of Gastroenterology, 2019)
-